RETROSPECTIVE STUDY EVALUATING THE EFFICACY OF LJ MEDIUM ALONG WITH PENICILLIN TO IMPROVE CULTURE YIELD OF MYCOBACTERIUM TUBERCULOSIS IN PATIENTS - BUKHARI, AA; KHAN, MSN; AKRAM, A; BUKHARI , AA; NAEEM, N; NAZ, A (Biological and Clinical Sciences Research Journal, 2023)
This study evaluated the efficacy of penicillin in improving the culture yield of M. Tuberculosis in cases of pulmonary tuberculosis. A retrospective study was conducted in the Department of Pathology, MMDC, Multan. A total of 350 suspected pulmonary tuberculosis patients were selected for the study. An early morning sputum specimen was collected. NAOH citrate and N-acetyl-L-cysteine were used for digesting, decontaminating, and homogenizing the sputum. The samples were processed on Lowenstein Jensen media and then Lowenstein Jensen media with penicillin. The cultures were then examined after 2 months. On LJ media, 100 (28.5%) suspected cases were positive, and 80 (22.8%) cases were contaminated. On LJ media with penicillin, 145 (41.4%) cases were positive, and 15 (4.3%) were contaminated. In addition, 30 (8.5%) were 1+ grading, 15 (4.3%) were 2+ grading on both media, 95 (27.1%) were 3+ grading on LJ media, and 50 (14.2%) were 3+ grading on LJ media with penicillin. Contamination in Mycobacterium tuberculosis is reduced by adding penicillin to the LJ media, and isolation-positive cultures are enhanced.